THE IMPORTANCE OF LEXICON IN LANGUAGE LEARNING - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
Our article discusses the importance of lexical intervention in learning a foreign language. She defines lexical intervention as a borrowing of lexemes from a foreign language into a bilingual language, which manifests itself either in the transfer of phonetic sequences from one language to another or in shifts in the meaning structure of the native language lexeme with scalped formations that correspond to models of foreign words.